Balatantram - A Book Review - Jiji N G; Braivin Camly R (International Journal of Ayurveda and Pharma Research, 2021)
Ayurveda the ancient Indian bioscience depicts all the aspects of healthy living. Kaumarabhrithya is a very important branch among the Ashtangas of Ayurveda. Balatantram is a valuable book in Balachikitsa written by Kalyana Vaidya in 16th Century. The work has 14 chapters, signified as Patala and has approximately 831 verses. Narration of Balatantram contains the principles and practices regarding the various aspects of diseases of children along with infertility related to males and females and Vajikarana upayas. This book is already published yet not very popular. This review would help the scientific community to understand this book in concise manner.